2008
DOI: 10.1089/ast.2007.0215
|View full text |Cite
|
Sign up to set email alerts
|

On the Survivability and Detectability of Terrestrial Meteorites on the Moon

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 31 publications
4
46
0
Order By: Relevance
“…Survivability of such projectile fragments to the Moon's surface may be possible at these collisional velocities and associated peak shock pressure regimes. However, preservation of impactor material will be facilitated further by relatively low (\4 km/s) impact velocities (Crawford et al 2008;Armstrong 2011), by oblique (\10 degrees) impact angles where material can be spalled off the projectile during impact (Pierazzo and Melosh 2000; Bland et al 2008;Svetsov and Shuvalov 2015;Schultz and Crawford 2016), and by incorporation of impactor material into central peaks formed during the crater formation process (Yue et al 2013). Recent laboratory experiments have also shown that the material properties, specifically porosity, of the impactor target material further helps to b Large FeNi metal assemblages found in a crystalline (plagioclase, pyroxene) impact melt breccia clast extracted from regolith breccia 60016.…”
Section: Asteroidsmentioning
confidence: 99%
See 3 more Smart Citations
“…Survivability of such projectile fragments to the Moon's surface may be possible at these collisional velocities and associated peak shock pressure regimes. However, preservation of impactor material will be facilitated further by relatively low (\4 km/s) impact velocities (Crawford et al 2008;Armstrong 2011), by oblique (\10 degrees) impact angles where material can be spalled off the projectile during impact (Pierazzo and Melosh 2000; Bland et al 2008;Svetsov and Shuvalov 2015;Schultz and Crawford 2016), and by incorporation of impactor material into central peaks formed during the crater formation process (Yue et al 2013). Recent laboratory experiments have also shown that the material properties, specifically porosity, of the impactor target material further helps to b Large FeNi metal assemblages found in a crystalline (plagioclase, pyroxene) impact melt breccia clast extracted from regolith breccia 60016.…”
Section: Asteroidsmentioning
confidence: 99%
“…Identification and preservation of ejected planetary material (e.g., from the early Earth during the Hadean or Archean, or Noachian Mars) could answer outstanding questions related to the early geological, and possibly biological, evolution of the terrestrial planets (e.g. Armstrong et al 2002;Crawford et al 2008;Matthewman et al 2015).…”
Section: Impactors Derived From Other Planetsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Moon may provide us with this archive (Armstrong et al, 2002;Crawford et al, 2008;Joy et al, 2012;Burchell et al, 2014b). Major surface volcanic activity on the Moon ceased around 3.1 Ga (Wilhelms et al, 1987).…”
Section: Organic Records In the Solar Systemmentioning
confidence: 99%